2019
DOI: 10.1016/j.ijwd.2019.04.021
|View full text |Cite
|
Sign up to set email alerts
|

Clinical considerations for the management of psoriasis in women

Abstract: The burden of psoriasis is particularly high for women, who report lower levels of happiness (women: 18.5%; men: 11.3% lower vs. general population) and are more likely to experience stress (women: > 60%; men: 42%), loneliness (women: 25-28%; men: 19-24%), stigmatization (Feelings of Stigmatization Questionnaire score; women: 93.2; men: 78.0), and reduced sexual activity (women: 33%; men: 19%) compared with men. The onset of psoriasis is bimodal, with one incidence peak (15-30 years) that coincides with the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
55
1
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(62 citation statements)
references
References 78 publications
3
55
1
3
Order By: Relevance
“…Although it is not thought to affect fertility, pregnancy rates have been observed to be approximately 22% lower in women with psoriasis. Among the reasons for this, it has been suggested that many factors such as women's unwillingness to voluntarily, concerns about pregnancy and/or postpartum disease activity, fear of the effect of psoriasis treatments on pregnancy and baby, as well decreased closeness due to embarrassment and/or physical inability play a role [8,11].…”
Section: Psoriasis and Pre-pregnancy Periodmentioning
confidence: 99%
See 3 more Smart Citations
“…Although it is not thought to affect fertility, pregnancy rates have been observed to be approximately 22% lower in women with psoriasis. Among the reasons for this, it has been suggested that many factors such as women's unwillingness to voluntarily, concerns about pregnancy and/or postpartum disease activity, fear of the effect of psoriasis treatments on pregnancy and baby, as well decreased closeness due to embarrassment and/or physical inability play a role [8,11].…”
Section: Psoriasis and Pre-pregnancy Periodmentioning
confidence: 99%
“…In a cohort study using prospective data There are still some diffi culties in treatment due to the lack of well-established guidelines in pregnant women with psoriasis. However, United States and European drug labeling now summarize safety data on pregnancy and lactation to inform treatment choice in this patient population [8,48].…”
Section: Pregnancy Course In Patients With Psoriasismentioning
confidence: 99%
See 2 more Smart Citations
“…6 However, 65% of patients reported worsening during the postpartum period. 6 Although well-designed guidelines on the treatment of psoriasis during pregnancy are lacking, 7 there are expert opinions and consensus recommendations. [8][9][10] Emollients and low-to-moderate-potency topical steroids are recommended as first-line therapy in limited disease, while narrowband ultraviolet B phototherapy as second-line therapy.…”
mentioning
confidence: 99%